Resid Pediatr 2022
DOI: 10.25060/residpediatr-2022.v12n2-322
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile of children and adolescents with type 1 diabetes mellitus

Abstract: INTRODUCTION: Cardiovascular diseases are the main cause of death in patients with type 1 diabetes mellitus (T1DM) and atherosclerotic process begins in childhood. OBJECTIVE: To evaluate lipid profile of patients with T1DM accompanied at the pediatric endocrinology (UEP), Hospital de Clínicas, Federal University of Paraná (HC-UFPR), the prevalence of dyslipidemia and its correlation with glycemic control, duration of T1DM, family history of dyslipidemia and nutritional profile status. METHODS: Data of diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Several studies with individuals with T1DM have evaluated the the prevalence of dyslipidemia and the duration of the disease. A pre found in patients with up to five years of diagnosis and 53.6% in pa years of diagnosis of T1DM [59]. Other studies have shown a pre indicates a significant effect of the model for p-value ≤ 0.050.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Several studies with individuals with T1DM have evaluated the the prevalence of dyslipidemia and the duration of the disease. A pre found in patients with up to five years of diagnosis and 53.6% in pa years of diagnosis of T1DM [59]. Other studies have shown a pre indicates a significant effect of the model for p-value ≤ 0.050.…”
Section: Discussionmentioning
confidence: 80%
“…Several studies with individuals with T1DM have evaluated the relationship between the prevalence of dyslipidemia and the duration of the disease. A prevalence of 37.1% was found in patients with up to five years of diagnosis and 53.6% in patients with up to ten years of diagnosis of T1DM [ 59 ]. Other studies have shown a prevalence of 26.2% in patients diagnosed with T1DM for 5.6 years [ 60 ] and 72.5% in patients with the disease for 10.6 years [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation